Ultraperformance Liquid Chromatography with Electrospray Ion Trap Mass Spectrometry for Chondroitin Disaccharide Analysis - Solakyildirim, Kemal (2009)
Chondroitin sulfate (CS) has an important role in cell division, in the central nervous system, and in joint related pathologies such as osteoarthritis. Due to the complex chemical structure and biological importance of CS, simple, sensitive, high-resolution, and robust analytical methods are needed for the analysis of CS disaccharides and oligosaccharides. An ion pairing, reversed-phase, ultraperformance liquid chromatography (IPRP-UPLC) separation, coupled to electrospray ionization mass spectrometry with ion trap mass analyzer was applied for the analyses of CS-derived disaccharides. UPLC separation technology utilizes small particle diameter, short column length, and elevated column temperature to obtain high resolution and sensitivity. Hexylamine (15 mM) was selected the optimal ion-pairing reagent.